Distributed applications and interoperable systems 11th IFIP WG 6.1 international conference, DAIS 2011, Reykjavik, Iceland, June 6-9, 2011. proceedings - Felber, Pascal; Rouvoy, Romain (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 11th IFIP WG 6.1 International Conference on Distributed Applications and Interoperable Systems, DAIS 2011, held in Reykjavik, Iceland, in June 2011 as one of the DisCoTec 2011 events.The 18 revised full papers and 6 short papers presented were carefully reviewed and selected from 55 submissions. The papers presented at DAIS 2011 address key challenges of modern distributed services and applications, including pervasiveness and peer-to-peer environments, and tackle issues related to adaptation, interoperability, availability and performance, as well as dependability and security.